2015
DOI: 10.1093/protein/gzv027
|View full text |Cite
|
Sign up to set email alerts
|

Studying protein fold evolution with hybrids of differently folded homologs

Abstract: To study the sequence determinants governing protein fold evolution, we generated hybrid sequences from two homologous proteins with 40% identity but different folds: Pfl 6 Cro, which has a mixed α + β structure, and Xfaso 1 Cro, which has an all α-helical structure. First, we first examined eight chimeric hybrids in which the more structurally conserved N-terminal half of one protein was fused to the more structurally divergent C-terminal half of the other. None of these chimeras folded, as judged by circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Among Cro bacteriophage transcription factors, a pair of homologous proteins with 40% sequence identity (indicating that they share a recent common ancestor) but different structures was found. Subsequent studies showed that some Cro proteins might be just a few mutations away from changing fold (18,21). Similarly, the structure of a protein naturally adopting a 3a fold was converted into a 4bþa fold via a series of carefully engineered point mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Among Cro bacteriophage transcription factors, a pair of homologous proteins with 40% sequence identity (indicating that they share a recent common ancestor) but different structures was found. Subsequent studies showed that some Cro proteins might be just a few mutations away from changing fold (18,21). Similarly, the structure of a protein naturally adopting a 3a fold was converted into a 4bþa fold via a series of carefully engineered point mutations.…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated by findings that long non-coding RNA may serve as a novelty pool and that ribosomes indeed translate novel ORFs [ 6 , 7 ]. It is hypothesized that this mechanism might produce novel domains or folds, which are added to existing genes or assembled to new genes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One particularly interesting aspect of this problem is revealed by the repeated observation of “chameleon sequences”, which can adopt different folds, and the emerging discovery of “metamorphic proteins”, which change fold as part of their function. Such extremes of conformational specificity, which have already been shown to be amenable to protein engineering, may prove to be an evolutionarily important mechanism for both fold change and functional versatility (as a prominent sub‐class of “moonlighting proteins”). However, current bioinformatics tools and molecular dynamics simulations, using sequence or structure information, fail to reliably identify chameleon or metamorphic proteins .…”
Section: Introductionmentioning
confidence: 99%